Fenestrated-Branch Endovascular Repair After Prior Abdominal Aortic Aneurysm Repair. (November 2021) - Juszczak, Maciej; Vezzosi, Massimo; Nasr, Hosaam; Claridge, Martin; Adam, Donald J.
Abstract : Objective: To report the outcome of fenestrated and branch endovascular aortic repair (FEVAR–BEVAR) for asymptomatic and acute symptomatic proximal aortic pathology in patients with prior open (OSR) or endovascular (EVAR) abdominal aortic aneurysm (AAA) repair. Methods: This was a single centre retrospective study of consecutive patients with non-ruptured (asymptomatic and acute symptomatic) proximal aortic pathology after prior OSR or EVAR treated between December 2007 and February 2020. The primary endpoint was 30 day/in hospital mortality. Secondary endpoints were technical success, primary clinical success, and Kaplan–Meier estimates of medium term survival and freedom from re-intervention. Data are presented as median (interquartile range [IQR]). The effect of covariates on medium term survival was estimated using multivariable (Cox proportional hazards model) analysis. A p value < .05 was considered to be statistically significant. Results: Ninety-two patients (83 men; median age 75 years [IQR 71 – 80 years]; median diameter 73 mm [IQR 64 – 89 mm]; 82 elective, 10 acute) underwent FEVAR–BEVAR after prior OSR ( n = 47) or EVAR ( n = 45). Indications for intervention were aneurysmal degeneration with or without type 1a endoleak ( n = 57; four juxtarenal [JR] AAA, 21 extent II/III, 32 extent IV thoraco-abdominal aortic aneurysms); type 1a endoleak alone ( n = 27) and to create a more durable repair after acute infrarenal EVAR ( n = 8; JRAAA). In total, 348 renovisceral vessels were targeted for preservation and 324 were stent grafted. Twenty-four unstented vessels comprised one bypass, 11 scallops and six fenestrations intentionally not stent grafted, two vessels occluded before graft implantation, and four vessels occluded intra-operatively. Primary technical success was 95.6%. The thirty day mortality rate was 1.1% and one patient each (1.1%) required permanent dialysis or developed temporary spinal cord ischaemia. Early primary clinical success was 94.6%. Median follow up was 36 months (IQR 23 – 64 months). Estimated overall survival (± standard error) at one, two, and three years was 86% ± 4%, 85% ± 4%, and 70% ± 5%, respectively. Multivariable analysis did not demonstrate any independent predictors of survival. Four target vessels occluded during follow up. Nineteen patients underwent 28 late re-interventions, with almost half performed for issues arising distal to the FEVAR–BEVAR. Patients treated with a cuff were statistically significantly more likely to require distal re-intervention compared with those treated by relining (9/49 vs. 1/43, p = .018 [odds ratio 9.3, 95% confidence interval 1.2 – 423]). In patients with prior EVAR alone, this did not reach statistical significance (cuff 7/25 vs. relining 1/20, p = .059 [odds ratio 7.1, 95% confidence interval 0.8 – 350]). Estimated freedom from re-intervention at one, two, and three years was 88% ± 3%, 81% ± 4%, and 81% ± 4%, respectively. Conclusion: FEVAR–BEVAR after prior OSR or EVAR is associated with low peri-operative morbidity and mortality, and acceptable medium term survival and freedom from re-intervention. Treatment with a FEVAR–BEVAR cuff is associated with a higher requirement for distal re-intervention than relining of the original repair.